Secret Nazi-Soviet Protocols of 1939 and Visions and Ways of Restoration/ Nonrestoration of Lithuanian lndependence - Šepetys, Nerijus (Lietuvos istorijos studijos, 2003)
First two pages missing.
Keywords: -